Tahfidz Teachers' Strategies in Improving the Memorization Skills of Slow Learners - Mustafa, Nurul Nadiah Binti; Elita, Rodia; Guspita, Rosi; Vanessa, Anadya Diva (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
The ability to memorize the Qur'an from an early age is an important part of Islamic education, especially in Islamic-based elementary education institutions. Integrated Islamic Elementary Schools (IIES) implement the tahfidz Al-Qur'an program as part of the learning curriculum. This study aims to determine the implementation of the tahfidz Al-Qur'an program in grade 4 at the Integrated Islamic Elementary School, which includes planning, implementation, and evaluation of the program. This study uses a qualitative approach method with a field research type, involving tahfidz teachers and students as primary data sources, and the principal and coordinator of the Al-Qur'an field as secondary data. Data collection techniques are carried out through interviews, observations, and documentation, with data analysis in the form of reduction, presentation, and conclusion. The results of the analysis show that there are three main strategies applied by tahfidz teachers in guiding students with special needs (slow learners) at the Integrated Islamic Elementary School, namely: i) personal approach strategy, ii) material delivery strategy, iii) motivation strategy. The results of the study can provide important implications for the development of more effective and structured tahfidz learning strategies at the elementary school level.